First case of pancreas transplant alone in a patient with diabetes and HIV infection. (December 2016) - Mittal, Shruti; Choudhary, Pratik; Callaghan, Chris; Hilton, Rachel; Drage, Martin
Chronic conditions have largely replaced opportunistic infections as the leading causes of mortality in human immunodeficiency virus (HIV) infection. Pancreas transplantation alone can be performed for people with difficult to manage diabetes associated with severe hypoglycaemic unawareness. For carefully selected patients, pancreas transplantation alone has the potential to dramatically improve quality and quantity of life. Historically, HIV was considered a contraindication to transplantation; however, today renal transplantation for people with end-stage kidney disease and HIV infection is increasingly common. We describe the use of a standard immunosuppression regimen in combination with effective antiretroviral control using a stable highly active antiretroviral therapy regimen with minimal interaction with immunosuppressants. We describe what is, to our knowledge, the first case of pancreas transplantation alone performed for this particularly challenging group, resulting in complete resolution of hypoglycaemic symptoms. We suggest that this group of patients should receive optimal diabetes management, including access to transplantation where appropriate, and demonstrate that pancreas transplantation alone is feasible for people with HIV infection.